MALAYSIA’S POLICY TOWARD ASIAN FINANCIAL CRISIS 1997-1998 UNDER MAHATHIR ERA - Ergi Fathurachman (HI 15 UMY 391, 2015)
*391 The advance development of Asian countries had been disturbed by the historical economic tragedy at that time. That historical economic tragedy called as the Asian financial crisis. The Asian financial crisis attacked several countries which has good economic development the 20th century. Asian financial crisis 1997-1998 has made the trigger for several countries to be in threat of bankruptcy. This crisis started from Thailand and spread to others countries rapidly. Malaysia was one of the countries which attacked by Asian Financial Crisis. Although Malaysia known as the new advanced industrial countries, it also has threatened by that crisis. Become interesting question, when the other attacked countries much longer than Malaysia in order to overcome the crisis at that time, but Malaysia had successful to overcome the Asian financial crisis rapidly. The success of Malaysia to overcome the crisis, become the interesting topic to be analysed. This undergraduate thesis will be analyze the different policies taken by Malaysia from the other attacked countries. High risk policy under the Mahathir era to overcome the crisis will be discussed in this undergraduate thesis. Several concepts and theory will be used to analyse this topic. Those concepts and theory that will be use are the concept of crisis, currency board system (CBS), Mahathiriskonomism, the concept of economic sovereignty and theory of financial crisis. Keyword: Mahathir Mohamad, Asian Financial Crisis, Malaysia’s Policy